Virus-Binding Proteins Recovered from Bacterial Culture Derived from Activated Sludge by Affinity Chromatography Assay Using a Viral Capsid Peptide - Sano, Daisuke (American Society for Microbiology, 2004)
The contamination of water environments by pathogenic viruses has raised concerns about outbreaks of viral infectious diseases in our society. Because conventional water and wastewater treatment systems are not effective enough to inactivate or remove pathogenic viruses, a new technology for virus removal needs to be developed. In this study, the virus-binding proteins (VBPs) in a bacterial culture derived from activated sludge were successfully recovered. The recovery of VBPs was achieved by applying extracted crude proteins from a bacterial culture to an affinity column in which a custom-made peptide of capsid protein from the poliovirus type 1 (PV1) Mahoney strain (H(2)N-DNPASTTNKDKL-COOH) was immobilized as a ligand. VBPs exhibited the ability to adsorb infectious particles of PV1 Sabin 1 as determined by enzyme-linked immunosorbent assay. The evaluation of surface charges of VBPs with ion-exchange chromatography found that a majority of VBP molecules had a net negative charge under the conditions of affinity chromatography. On the other hand, a calculated isoelectric point implied that the viral peptide in the affinity column was also charged negatively. As a result, the adsorption of the VBPs to the viral peptide in the affinity column occurred with a strong attractive force that was able to overcome the electrostatic repulsive force. Two-dimensional electrophoresis revealed that the isolated VBPs include a number of proteins, and their molecular masses were widely distributed but smaller than 100 kDa. Amino acid sequences of N termini of five VBPs were determined. Homology searches for the N termini against all protein sequences in the National Center for Biotechnology Information (NCBI) database showed that the isolated VBPs in this study were newly discovered proteins. These VBPs that originated with bacteria in activated sludge might be stable, because they are existing in the environment of wastewater treatments. Therefore, a virus removal technology utilizing VBPs as viral adsorbents can be developed, since it is possible to replicate VBPs by protein cloning techniques.